Analysis of the Influence of Service Quality and Comfort on Geprek John HK Customer Satisfaction: Analisis Pengaruh Kualitas Pelayanan dan Kenyamanan Terhadap Kepuasan Pelanggan Geprek John HK - Faizzatur Rochma; Afifatus Sholikhah (Universitas Nahdlatul Ulama Sidoarjo, 2024)
The culinary industry is one of the assets that is developing nowadays along with changes in lifestyle and consumer preferences. One of the culinary industries that is developing at the moment is geprek Jhon HK which is unique with its geprek chicken. The aim of this research is to determine the level of service quality and comfort that influence customer satisfaction at Geprek John HK. The method used in this research is a quantitative method and the respondents in this research are 45 Jhon HK geprek consumers. The results of this research are that there is a linear relationship between comfort and customer satisfaction, and there are no multicollinearity, autocorrelation or heteroscedasticity problems in the regression model. And the conclusion is that service quality and comfort have a positive influence on customer satisfaction.